BENTUK INTERAKSI SOSIAL ANTAR MAHASISWA PENERIMA BEASISWABIDIKMISI DI ASRAMA PUTRI PGSD FKIP UNIVERSITAS TANJUNGPURA - Murni, Murni; Zakso, Amrazi; Budjang, Gusti (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aims to the forms of social interaction among scholarship recipients of Bidikmisi students in PGSD female’s dormitory FKIP Tanjungpura University. The method used in this research is a qualitative descriptive method. The data collection techniques used are observation techniques, interviews, and documentation studies. The data collection tools used are observation guides, interview guides, and documentation.The informant in this study was the chairman of the dormitory manager and the female dormitory resident.The results showed that as a whole, the form of social interaction among scholarship recipients of Bidikmisi students in PGSD female’s dormitory in PGSD FKIP Untan more leads to an associative social process. Although there are still found abuses or conflicts between dorm occupants, but they are still able to solve their own problems in a family without seeking outside help. Keywords: Form of Social Interaction,  Associative Social Processes, Dissociative  Social Processes